BALIQ: INDIGENOUS CONFLICT RESOLUTION MECHANISM AMONG THE SILTE PEOPLE: THE CASE OF SILTI WOREDA, KIBET TOWN - KEBEDE LEMU BEKELCHA; AREGASH ETICHA SEFERA; LENSA TUFA FOGI (International Journal of Innovations in Engineering Research and Technology, 2021)
The different ethnic groups in Ethiopia have developed their own indigenous mechanism to deal with conflicts. The Silte of southern Ethiopia is among those ethnic groups with their own conflict resolution mechanism. The main purpose of this study is to explore the indigenous institutions of conflict resolution among the Silte people of southern Ethiopia. This study has employed a qualitative research to meet the stated objectives of the study. To achieve the above objectives, the study collected primary data from different informants in Silte Woreda by employing such qualitative data collection techniques as an interview, focus group discussions and observation. The secondary data sources were obtained from published and unpublished government documents; such as books and magazine and. The finding of this research reveals that the indigenous conflict resolution institution is one of the ways of resolving conflict in the study area. The study also came up with the major causes of conflict in the study area and the indigenous means to resolve them through the Baliq conflict resolution institution. The major causes that drive people of the study area in to conflict are family related conflicts, land, theft, marriage and insult. This research also exposes the criterion for the selection of an elder in conflict resolution institution and the study areas indigenous rules of law enforcement. It also came up with the relationship that existed between ICRM and the formal court system in resolving conflicts and keeping the societies peace and security. Hence, Baliq plays a core role in resolving conflicts.